Detection of Beta-Lactamases (ESBL and MBL) Producing Gram-Negative Pathogens in National Public Health Laboratory of Nepal - Anjana Shrestha; Jyoti Acharya; Jyoti Amatya; Rabin Paudyal; Nisha Rijal (International Journal of Microbiology)
Background. Bacterial resistance to antibiotics has increased in recent years. Resistance to β-lactams in Gram-negative bacteria has been reported to be associated with extended spectrum beta-lactamases and metallo-beta-lactamases. This study was aimed at determining the distribution and antibiotic susceptibility patterns of Gram-negative pathogens producing extended spectrum beta lactamases and metallo-beta lactamases. Method and Methodology. This cross-sectional study was conducted at the National Public Health Laboratory during a period of six months. All clinical specimens were obtained and processed for the identification of Gram-negative pathogens by culture, morphological, and biochemical tests. Antibiotic susceptibility testing of the isolates was performed by the Kirby Bauer disc diffusion and the isolates were tested for ESBL and MBL by the combined disk method. Results. Out of 4266 clinical specimens, 197 (4.6%) were found to be Gram-negative bacterial isolates. 47 (23.9%) isolates were ESBL producers. The most predominant organisms were Escherichia coli (53%), Klebsiella pneumonia (23%), and Pseudomonas spp. (13%). 16 (8.2%) were positive for MBL producers, and 6(3.1%) were both ESBL and MBL producers. The MBL activity was seen in E. coli (38%), followed by Pseudomonas spp. (31%), and K. pneumoniae (19%). The ESBL producers showed a higher degree of sensitivity towards imipenem and amikacin, followed by piperacillin tazobactam. MBL producers showed sensitivity towards amikacin only. Conclusion. The prevalence of ESBL and MBL producing Gram-negative bacteria was found to be high in bacterial infections in Nepal. Routine laboratory testing for ESBL and MBL is needed in order to optimize antibiotic management and reduce the risk of spread of infections caused by ESBL and MBL producers.